ANALISIS FATWA DSN-MUI TENTANG AKAD MURABAHAH DALAM PENERAPAN HAK MILIK (BANK SUMUT SYARIAH PERDAGANGAN) - Nazlah Yuningsih (Jurnal Al Wadiah, 2023)
The issue of this investigation lies in the Murabahah agreement in the implementation of property rights as regulated in DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000 concerning Murabahah. The Murabahah fatwa states: "The bank purchases goods needed by its customers on behalf of itself, and the purchase is legal and free from usury. "In fact, banks as sellers give their customers the freedom to buy goods." The aim of this research is to find out whether the implementation of the Murabahah contract at PT Bank Sumut Syariah Capem Trading is in accordance with DSN-MUI Fatwa No. 04/DSN-MUI/IV/2000 concerning Murabahah. The type of research used in this research is field research, the research approach used in this research is qualitative research, and the data collection methods are observation, interviews and documentation. In analyzing the application of property rights in Murabahah contracts at PT. Bank Sumut Syariah Capem Trading considers that if a Murabahah object legally becomes the property of Bank Sumut, then a Murabahah agreement is entered into with the customer and the previous bank. Murabahah ownership of the object belonging to it is transferred and then becomes the property of the customer. This is of course in accordance with the DSN-MUI fatwa number 04/DSN-MUI/IV/2000 concerning Murabahah.